ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN MC DONALD'S DI KOTA SEMARANG - Fitriana, Fitriana (Master of Management Diponegoro University, 2012)
The objectives of the study is to analyze the factor influence towards the loyalty of customers of Mc Donald in the study area. This research was conducted in all Mc Donald outlets in Semarang.The method of purposive sampling was employed to with drawn of. The data were analyze usng Moderated Structural Equation Model (MSEM) with software Amos 16.0. The sample (110 respondents).The results shown that the quality of product Â and also a service quality have positive impact to the customers satisfaction. Further, the satisfaction is positively affected to customers loyalty. The Mc Donald outlets in the Semarang suggests that should consider for improving the customers loyalty.